BANKING SECTOR PERFORMANCE, PROFITABILITY, AND EFFICIENCY: A CITATION‐BASED SYSTEMATIC LITERATURE REVIEW. (6th December 2019) - Ahmad, Nisar; Naveed, Amjad; Ahmad, Shabbir; Butt, Irfan
Abstract: This study presents a citation‐based systematic literature review on banking sector performance, particularly in terms of profitability, productivity, and efficiency. Specifically, the study aims to identify the leading sources of knowledge in terms of the most influential journals, authors, and papers. The paper presents a content analysis of the 100 most cited papers. In total, 1996 peer‐review papers were found relevant in the Scopus database by using a comprehensive list of keywords. The results show that the Journal of Banking & Finance appears to be the leading journal in terms of publication count and citations. Based on total citations, Allen Berger is the most prolific author. The most cited paper is "Problem loans and cost efficiency in commercial banks" by Allan Berger and Robert DeYoung. The content analysis of the top 100 papers identifies five essential themes: determinants of efficiency, methodology, ownership, financial crises, and scale economies. In terms of estimation approaches, 74% of papers employed frontier analysis, which includes 34% parametric and 40% nonparametric methods, and remaining 26% have used financial ratio analysis. Additionally, stochastic frontier and data envelopment analysis are widely used in parametric and nonparametric methods, respectively. An intermediate approach is extensively adopted for the specification of inputs and outputs.